Introduction to Mental Health in Healthcare Workplaces - Ruby Brown and Anne Wojtak (Healthcare Quarterly, 2024)
Healthcare organizations are increasingly aware of the urgency to address the needs of their workforce as part of a broader strategy to promote well-being and improve patient care. This issue of Healthcare Quarterly brings forward promising approaches and resources for establishing healthy workplaces.
Keywords: healthy workplaces, Quintuple Aim, National Standard of Canada for Psychological Health and Safety in the Workplace, well-being, patient care, healthcare organizations